Influência da variação do TDH e da taxa recirculação no comportamento de reatores anaeróbio e aeróbio de leito fixo seguidos de filtro percolador na remoção de nitrogênio e fósforo - Gatti, Raphael Augusto Ferreira (2017)
With the increase of the population and the undue discharge of sanitary sewage without adequate treatment, there is an increase of the carbonaceous, nitrogenous and phosphorus loads which can lead to the eutrophication of water bodies. There are several treatment processes, but the application of biological processes, in most of cases, is the most viable alternative in Brazil. However, there is a need for post-treatment, mainly for the removal of nitrogen and phosphorus in order to achieve the standards established in the current environmental legislation. The objective of this work is to evaluate the behavior of a system composed by an anaerobic reactor (20 L), followed by an aerobic reactor (19 L), filled with corrugated rings of Polyvinyl chloride (PVC) as the fixed bed, followed by a trickling filter (16 L) filled with red clay. The system was subjected to the variation of the hydraulic retention time (HRT) and the recirculation rate (R), operated in series with upflow and continuous flow. Recirculation ratios of 150, 100 and 50% and HRT of 5, 7 and 9 h with constant aeration flow rate of 10 L min-1 were tested. For the evaluation of the system, were determined the liquid temperature, pH, total and bicarbonate alkalinity, volatile acids, dissolved oxygen (OD), chemical oxygen demand (COD), biochemical oxygen demand (BOD), total Kjeldahl nitrogen (TKN), ammoniacal nitrogen, nitrite, nitrate and total phosphorus. The removal efficiencies achieved by the system were - 98, 98 and 99% to the raw COD, 96, 89 and 87% to TKN and 78, 82 and 77% to phosphorus, when operated with recirculation rates of 150, 100 and 50%, respectively. Regarding the HRT variation in 5, 7 and 9 h, the removal efficiencies obtained were 86, 96 and 98% to the raw COD, 90, 93 and 94% to NTK and 74, 89 and 95 % to total phosphorus, respectively. With the results obtained, it was possible to conclude that the best operational condition was with recirculation ratio of 150% and HRT of 5 h. With the statistical analysis, by means of the central composite rotational design (CCRD) and the desirability, it was possible to obtain the optimal condition of operation with HRT of 5 h and recirculation rate of 123%. It was also possible to validate the statistical models for nitrification, denitrification, total nitrogen removal and phosphorus removal to the operational conditions evaluated.